Implementasi Kurikulum Merdeka dalam Pembelajaran Sejarah Kebudayaan Islam di MTsN 9 Agam - Gustina, Nadia; Yusmanidar, Yusmanidar; Eriyanti, Eriyanti; Demina, Demina (Indo-MathEdu Intellectuals Journal, 2025)
The main objective of this research is to describe how the Merdeka Curriculum is implemented in various aspects of the curriculum, such as the formulation of learning objectives, the development of materials, the use of methods, the organization of the curriculum structure, and the forms of evaluation used. This research employs a qualitative approach with a phenomenological method. The main technique used is in-depth interviews to explore subjective experiences. The data analysis process is carried out through stages of data condensation, data presentation, and drawing conclusions. The research results show that SKI learning at MTsN 9 Agam has adopted the principles of the Merdeka Curriculum, and teachers actively implement this curriculum by adjusting learning objectives to Learning Outcomes (CP), Learning Objectives Pathway (ATP), and indicators of achieving these objectives. Material development is carried out collaboratively by SKI teachers together with the MGMP forum, by reviewing materials from the previous curriculum and reorganizing them to align with the Merdeka Curriculum approach. In practice, teachers use various learning strategies such as interactive lectures, group discussions, Q&A sessions, role-playing, and activity-based projects. Learning evaluation is conducted by combining formative and summative assessments to evaluate both the process and the overall learning outcomes of students.